2012
DOI: 10.2217/epi.12.8
|View full text |Cite
|
Sign up to set email alerts
|

MacroH2A in Stem Cells: A Story Beyond Gene Repression

Abstract: The importance of epigenetic mechanisms is most clearly illustrated during early development when a totipotent cell goes through multiple cell fate transitions to form the many different cell types and tissues that constitute the embryo and the adult. The exchange of a canonical H2A histone for the ‘repressive’ macroH2A variant is one of the most striking epigenetic chromatin alterations that can occur at the level of the nucleosome. Here, we discuss recent data on macroH2A in zebrafish and mouse embryos, in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…While the genomic distribution of macroH2A correlates with suppression of transcriptional activity (Changolkar and Pehrson, 2006;Changolkar et al, 2010;Gamble et al, 2010), it is in some cases required for signal-induced gene activation (discussed in Creppe et al, 2012b). The repressive function of macroH2A proteins has been primarily associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…While the genomic distribution of macroH2A correlates with suppression of transcriptional activity (Changolkar and Pehrson, 2006;Changolkar et al, 2010;Gamble et al, 2010), it is in some cases required for signal-induced gene activation (discussed in Creppe et al, 2012b). The repressive function of macroH2A proteins has been primarily associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MacroH2A1 plays important roles in either positively or negatively regulating transcription by recruiting transcriptional coregulators such as PARP-1, PELP1, CBP and HDAC1 (Chakravarthy et al, 2005; Chen et al, 2014; Gamble et al, 2010; Hussey et al, 2014). MacroH2A1 functions in a variety of physiological and pathological processes including senescence, tumor suppression, inhibiting proliferation and inhibiting stem cell reprogramming (Cantariño et al, 2013; Creppe et al, 2012; Gamble and Kraus, 2010; Kreiling et al, 2011; Novikov et al, 2011; Sporn et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Based on these observations, it was initially suggested that the major function of macroH2A was that of transcriptional repression. However, evidence has accumulated ever since indicating that macroH2A is associated to the active state of a subset of genes, 10,12,13 suggesting that it might play a general structural role that, if perturbed, could affect transcription.…”
Section: Introductionmentioning
confidence: 99%